2005
DOI: 10.1111/j.1365-2036.2005.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 5‐aminosalicylate nephrotoxicity in the United Kingdom

Abstract: SUMMARYAim: To study 5-aminosalicylate nephrotoxicity in patients with inflammatory bowel disease in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 22 publications
(67 reference statements)
1
39
0
1
Order By: Relevance
“…More recently, data from the UK General Practice Research Database were used to estimate the incidence of renal disease in patients with IBD in a nested case-control analysis 17 : among the 19,025 5-ASA users with IBD, 130 patients developed renal disease (incidence rate of 0.17 cases per 100 patients per year), while the incidence among patients with IBD but without 5-ASA use was 0.25 and among patients without IBD was 0.08. Also in 2004, in a large European registry containing more than 1500 patients with IBD, reported during a follow-up of 1 year that the incidence of renal failure was not increased in patients using 5-ASA 16 (decreased creatinine clearance was observed in 34 patients, among them 13 with chronic renal impairment; comparing patients with and without renal impairment, no difference 24 : the authors estimated that the incidence of clinical nephrotoxicity in patients taking 5-ASA therapy was Ϸ1 in 4000 patients/year only. Studies with 5-ASA treatment in which serum creatinine or creatinine clearance was measured regularly are summarized in Table 2, 9,[13][14][15]18, where it is shown that nephrotoxicity was exceptional, being reported in few studies.…”
Section: Epidemiological Studies Evaluating Nephrotoxicity In Ibd Patmentioning
confidence: 90%
See 1 more Smart Citation
“…More recently, data from the UK General Practice Research Database were used to estimate the incidence of renal disease in patients with IBD in a nested case-control analysis 17 : among the 19,025 5-ASA users with IBD, 130 patients developed renal disease (incidence rate of 0.17 cases per 100 patients per year), while the incidence among patients with IBD but without 5-ASA use was 0.25 and among patients without IBD was 0.08. Also in 2004, in a large European registry containing more than 1500 patients with IBD, reported during a follow-up of 1 year that the incidence of renal failure was not increased in patients using 5-ASA 16 (decreased creatinine clearance was observed in 34 patients, among them 13 with chronic renal impairment; comparing patients with and without renal impairment, no difference 24 : the authors estimated that the incidence of clinical nephrotoxicity in patients taking 5-ASA therapy was Ϸ1 in 4000 patients/year only. Studies with 5-ASA treatment in which serum creatinine or creatinine clearance was measured regularly are summarized in Table 2, 9,[13][14][15]18, where it is shown that nephrotoxicity was exceptional, being reported in few studies.…”
Section: Epidemiological Studies Evaluating Nephrotoxicity In Ibd Patmentioning
confidence: 90%
“…Therefore, more studies are necessary to determine whether serum creatinine gives sufficient warning of nephrotoxicity or whether more elaborate tests of renal function are required. 24 Finally, it should be emphasized that there is no evidence to date that either the test, or the frequency of testing, is effective in identifying these patients at risk of developing 5-ASA-related renal impairment, and therefore there are no firm recommendations, supported by medical evidence, for renal function monitoring (type and frequency) in IBD patients treated with these drugs. Moreover, the aforementioned "recommendations" regarding screening for renal impairment should be considered as "suggestions" and not as medically necessary based on the review of the literature, as there is presently no evidence that such screening or monitoring improves patient outcomes.…”
Section: Recommendations For Renal Function Monitoring In Ibd Patientmentioning
confidence: 99%
“…Finally, in patients the degree of intestinal inflammation affects mesalazine pharmacokinetics [26]. Further research is needed to improve our understanding of the fate of mesalazine in the human body in order to assess a rationale for individual dose optimisation, with the chance to improve the risk/benefit ratio of this drug and maybe also to to reduce the risk for rare adverse effects such as interstitial nephritis [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, patients can develop worsening of their colitis symptoms, sometimes associated with fever and rash [ 8 ]. Nephrotoxicity is also a rare side effect, most often caused by acute or chronic interstitial nephritis with a risk of approximately 1 per 4,000 patients per year, and so renal function should be monitored periodically during therapy [ 9 ].…”
Section: Aminosalicylatesmentioning
confidence: 99%